Global research status and hotspots of radiotherapy for prostate cancer: a bibliometric analysis based on Web of Science from 2010-2022 - Xie, Xiaodu; Zhang, Peng; Ran, Chongjun; Liu, Lumiao; Hu, Jian; Lei, Pan; Liang, Peihe (Frontiers in Oncology, 2023)
Background: Radiotherapy (RT) is one of the important treatments for various cancer types and its application to prostate cancer (PCa) has also gradually gained increasing attention. However, there is a lack of comprehensive and objective studies on the overall status of research on RT for PCa. This article aims to summarize and quantify the dynamic trends of RT in PCa by using bibliometrics. Methods: Studies on RT for PCa were screened from the Web of Science Core Collection (WoSCC) database between 1 January 2010 and 21 November 2022 to collate and quantify information characteristics by analyzing parameters including annual publications, countries/regions, institutions and authors with the aid of the bibliometric software CiteSpace and VOSviewer. In addition, research trends and hotspots were explored by analyzing keywords and co-cited references. Results: A total of 21338 documents were retrieved. The United States of America (USA) ranked first and maintained the leading position among all countries in the number of publications (8489) and total citations (266342). The University of Toronto was the most active institution in total publications (n=587). Paul L Nguyen enjoyed the most publications (n=179), and Michael J Zelefsky enjoyed the most co-citations (n=3376). INTERNATIONAL JOURNAL OF RADIATION ONCOLOGY BIOLOGY PHYSICS published the most papers (n=1026), and was the most frequently co-cited journal (n=78550). The largest and closest cluster in the reference cluster analysis was “oligorecurrent prostate cancer”. The timeline view of keywords reveals that cluster “biochemical recurrence(BCR)” is ongoing. Moreover, keywords burstness analysis showed that "radiation dosimetry", "dose rate brachytherapy(BT)", "salvage radiotherapy", “stereotactic body radiotherapy(SBRT)”, “guideline”, and “multicenter” were the terms with great bursts in the past a few years. Conclusion: The application of RT targeting oligometastatic prostate cancer(OMPC) has garnered considerable attention among researchers. SBRT and BT have become hot topics in the field. Additionally, the BCR of PCa has long been a critical issue requiring extensive research and resolution, and salvage radiotherapy has currently emerged as a closely related research focus. Related large-scale multicenter studies have been conducted over the past few years, providing valuable insights. More high-quality research is expected to be employed to guide clinical decision-making.